Work values of generation Y - Faizah Indriyana; Indi Djastuti (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
There are about 38.83% of Indonesian workforces who are include in generation Y and this is more than the number of the other generations. The rush of global markets will create a new management approach that includes the generation Y’s interest on work aspects. So, this study aims to analyze the differences of generation Y’s work values based on gender and work status. The study also explores which predictors variable that has the strongest discriminant for generation Y’s work values based on gender and works status. The number of the sample used in this research is 137 Millennial by using nonprobability sampling. This study uses discriminant analysis with the help of SPSS version 23. Independent variables in this study are intrinsic work values, extrinsic work values, social/altruistic work values, and prestige work values. The dependent variables used in this study are the gender of generation Y and work status of generation Y. Two dependent variables this study used two model of discriminant in testing the research hypothesis. The result of analysis indicates that there are significant differences between generation Y by gender and work status. Generation Y’s work values based on gender and work status have the strongest discriminator variables on extrinsic work values.